Profesionalisme Kerja Kelompok Tani Pengelola Bunga Potong Krisan di Kota Tomohon - Mangundap, Vera Henny; Mingkid, Elvie; Londa, Very Y. (JURNAL ILMIAH SOCIETY, 2015)
Farmer groups as a forum for organizations and cooperate among members has a very important role in the life of a farm community, because of all the activities and problems in trying farmer carried out by the group simultaneously. One of the work done by the farmer groups in Tomohon is in the management of cut flowers such as roses, carnations, gladiolus, chrysanthemum, antherium, daisies, Hébras, tuberose, orchid, lily, Alstromeria, and molucella.This study was conducted to elucidate the cause of professionalism farmers group manager Chrysanthemum cut flower in Tomohon has not been achieved as a development resource management of scientific development, especially in the study of resource management. Through the use of qualitative methods found that professionalism farmer groups in pengelolah Krista cut flowers in Tomohon has not been achieved yet terbuntuknya caused by the commitment, creativity, innovation and responsiveness.Keywords: Professionalism, Farmers Group, Chrysanthemum.